2013
DOI: 10.1002/pat.3177
|View full text |Cite
|
Sign up to set email alerts
|

SALS, WAXS and mechanical properties of heat‐treated thermotropic polymers

Abstract: The influence of heat treatment on the texture, microstructure and tensile mechanical properties of extruded thin films of a series of high-performance thermotropic liquid crystal polymers (LCPs) was investigated. LCPs based on random units of hydroxybenzoic acid (B), hydroxynaphthoic acid (N), terephthalic acid (TA) and biphenol (BP) were kindly supplied by the former Hoechst Celanese Corp as 50 μm thick extruded tapes. The LCPs, denoted B-N, COTBP and RD1000, have B and N as common comonomers and vary the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Previously, it was shown that thermal treatment produced secondary endotherms and an initial increase of melting (solid‐to‐nematic, T s→n ) temperature, in agreement with other studies . Thermogravimetric analysis was also carried out to determine the influence of thermal treatment on thermal stability of B–N; the results are shown in Fig.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Previously, it was shown that thermal treatment produced secondary endotherms and an initial increase of melting (solid‐to‐nematic, T s→n ) temperature, in agreement with other studies . Thermogravimetric analysis was also carried out to determine the influence of thermal treatment on thermal stability of B–N; the results are shown in Fig.…”
Section: Resultssupporting
confidence: 91%
“…Uniaxial tensile testing carried out at room temperature showed that the elastic Young's modulus of B–N increased as a function of heat treatment time, thus correlating with increase of degree of crystallinity. Here, we further investigated the consequences of heat treatment by carrying out microindentation testing to determine the microhardness, H , of B–N copolyester.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations